THE EFFECT OF JOB SATISFACTION ON ORGANIZATIONAL COMMITMENT IN CLASS IIB CORRECTIONAL FACILITY CILACAP - Devi, Annisa Kartika; Rachmayanthy, Rachmayanthy (Universitas Nusa Cendana, 2025)
This research intends to investigate how contentment with one's work affects loyalty to the institution in Class 2B Correctional Facility Cilacap. Using a complete sample strategy, 61 workers were surveyed to gather primary data for this quantitative investigation. SPSS 27 was used to process the data that had been obtained. This research found that work satisfaction affected organizational commitment among employees to a degree of 59.3%, with other factors accounting for the remaining 40.7%. Class 2B Correctional Facility Cilacap personnel's organizational engagement may be further studied in the future by examining additional factors, such as workload and career administration. Keywords: Correctional Officer; Job Satisfaction; Organizational Commitment